Pengaruh Persepsi Orang Tua tentang Matematika terhadap Kemampuan Kognitif Siswa SD dalam Pembelajaran Matematika - Holisiah, Dwi Nova; Kusumastuti, Fitri Annisa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This research aims to determine the influence of parents’ perception of mathematics lessons on elementary school students’ cognitive abilities in learning mathematics. The research method used is associative quantitative with simple regression analysis techniques. The research subjects were 30 elementary school student and their parents who were selected purposively. Data was obtained through parent perception questionnaires and tests of students’ cognitive abilities in the form of mathematics questions adapted to the cognitive thinking level of elementary school students. Data analysis was carried out with the help of the SPSS program to determine the positive and significant relationship and influence between parents’ perceptions of mathematics and students’ cognitive abilities. This shows that positive parental perceptions can support children’s cognitive achievements in mathematics. This research also opens up opportunities for further research to examine other factors that influence student learning outcomes in more depth.Penelitian ini berupaya untuk mengetahui pengaruh persepsi orang tua terhadap pelajaran matematika terhadap kemampuan kognitif siswa SD dalam pembelajaran matematika. Metode penelitian yang digunakan adalah kuantitatif asosiatif dengan teknik analisis regresi sederhana. Subjek penelitian adalah 30 siswa SD dan orang tua mereka yang dipilih secara purposive. Data diperoleh melalui angket persepsi orang tua dan tes kemampuan kognitif siswa dalam bentuk soal matematika yang disesuaikan dengan tingkat berfikir kognitif siswa sekolah dasar. Analisis data dilakukan dengan bantuan program SPSS untuk mengetahui hubungan dan pengaruh antar variabel. Hasil penelitian menunjukkan bahwa terdapat pengaruh positif dan signifikan antara persepsi orang tua terhadap matematika dan kemampuan kognitif siswa. Hal ini menunjukkan bahwa persepsi orang tua yang positif dapat mendukung pencapaian kognitif anak di bidang matematika. Penelitian ini juga membuka peluang bagi peneliti lanjutan untuk mengkaji faktor lain yang turut memengaruhi hasil belajar siswa secara lebih mendalam.